ANTI-CORRUPTION CONTRACTUAL STRATEGIES IN ROAD CONSTRUCTION - A COMPARATIVE ANALYSIS BETWEEN BULGARIA AND AUSTRALIA - Steliyanov, Metodiy; Georgieva, Martina (E-Journal VFU, 2025)
Despite the foundational differences between the codified nature of Bulgarian law versus the common law basis of Australian contract law, the research identifies valuable practices that Bulgaria could adopt from Australia to enhance the integrity of contract relationships within its construction industry. The report points out the Australian framework, which significantly mitigates corruption risks during the procurement and execution phases of the construction projects, reflecting its high standing in international corruption perception indices. Conversely, Bulgarian anti-corruption contractual framework contains less rigorous enforcement mechanisms. The study suggests adoption of elements from Australia’s contractual and regulatory approaches with the use of AI for enhanced introduction of the measures and effectiveness of its construction sector.